ANALISIS KEBUTUHAN SUMBER DAYA MANUSIA UNIT REKAM MEDIS PETUGAS PENGELOLAAN DATA DENGAN METODE WISN (WORKLOAD INDICATOR STAFF NEED) GUNA MENUNJANG EFEKTIVITAS KERJA DI RSU BINA SEHAT BANDUNG - Farida Gustini; Tia Sentiana (Jurnal Infokes, 2020)
This research aimed to find out analysis requitment of human resources unit medical record of data management officer using WISN (Workload Indicator Staff Need) Method to support the effectiveness of work at Rumah Sakit Umum Bina Sehat Bandung. This research used qualitative method with descriptive approach while the data collection technique that the writer used was observation, interview and literate study that had close relevance with subject matter.  From the research that has been done, there are some problems, namely : (1) Lack of education and training on working time, (2) unit of work and categories of human resources unit medical record that does not meet the classification, (3) the availability of personnel data management. The suggestions given : (1) Dispatch officer of medical record to abreast education and training, (2) Accept DIII medical record as medical recorder, (3) Addition of human resources unit medical records data management officer as many four people.